Tick Size, Spread, and Volume - Ahn, Hee-Joon; Cao, Charles Q.; Choe, Hyuk (Journal of Financial Intermediation, 1996)
The AMEX changed the tick size from[formula]to[formula]for low-price stocks on September 3, 1992. Consistent with the prediction of L. E. Harris (1994, Minimum price variations, discrete bid–ask spreads, and quotation sizes,Rev. Finan. Stud.7,149–178), the change has reduced both quoted and effective spreads, although the magnitude of the reduction is much smaller than predicted. However, we fail to find evidence of a significant increase in trading volume. Our cross-sectional regressions show that stocks with greater trading activity, lower prices, and stronger competition from the regional exchanges experienced greater spread reductions.Journal of Economic LiteratureClassification Numbers: G10, G18, G20.